Mexico's Film History Overview - Montero, R.; Boampong, J. (My University, 2016)
The presentation will give a panoramic account of the development of Mexican cinema through the experiences of film director and scriptwriter, Rafael Montero. With a career in the industry spanning more than twenty-five years, Montero discusses his work which is very much attuned to the political, socio-economic, and cultural developments of Mexico.
Seminar
Keywords: panoramic account; Mexican cinema; socio-economic; cultural developments; Mexico